2020
DOI: 10.1029/2020wr027473
|View full text |Cite
|
Sign up to set email alerts
|

Using Unsupervised Machine Learning to Characterize Capillary Flow and Residual Trapping

Abstract: Recent research has highlighted the impact mesoscale heterogeneity can have on larger‐scale multiphase fluid flow properties. However, currently, there is no consensus on how to quickly and reliably analyze coreflooding experimental data to gain insights into mesoscale capillary‐dominated flow behaviors and how rock petrophysical properties affect such behaviors. In this study, we combine a machine learning‐based clustering method with physics‐based hypothesis testing to analyze multistage steady‐state coreflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…) but still within the strongly capillary-dominated flow regime (Jackson & Krevor, 2020;Ni & Benson, 2020;Ni et al, 2021).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…) but still within the strongly capillary-dominated flow regime (Jackson & Krevor, 2020;Ni & Benson, 2020;Ni et al, 2021).…”
Section: Methodsmentioning
confidence: 98%
“…The clustering algorithm is applied directly on the pixel-wise NWP saturation time series data without any statistical preprocessing or feature extraction steps (Ni & Benson, 2020). After clustering is done, we compute the cluster NWP volume time series by multiplying the cluster mean (arithmetic) NWP saturation by the cluster pore volume.…”
Section: Time Series Clustering Analysismentioning
confidence: 99%
“…Each voxel was treated as one data point, and the time series properties at each voxel were treated as individual attributes (i.e., CO 2 saturation time series). The CO 2 saturation and the porosity maps were obtained through CT image manipulation, and the voxel-level permeability map was obtained using the extended Krause's method 199 . This study tested two clustering methods and found that K-means clustering was more suitable for characterizing flow behaviours and hierarchical clustering was more desirable for identifying the capillary heterogeneity trapping behaviours.…”
Section: Co 2 Storagementioning
confidence: 99%
“…As an example application of this algorithm in porous material research, Ni and Benson (2020) used both k ‐means and agglomerative hierarchical clustering algorithm on time series data to characterize flow and trapping behavior of normalCnormalO2 during core flooding process. The goal was to describe that flow mechanisms are capillary or viscous dominated.…”
Section: Data Classification and Clusteringmentioning
confidence: 99%